Implementation of Social Cognitive Theory on Smoking Cessation - Zain Nadaa Nisriina; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Most people have understood the negative effects of smoking behavior, but not all of them can make the decision to stop the behavior. Like smoking behavior, quitting smoking is also influenced by various factors. This study aimed to analyze smoking cessation behavior in individuals who have quit smoking through Social Cognitive Theory in the Semarang City area. Subjects and Method: The study was conducted with a cross-sectional study design involving as many as 205 participants, including 123 active smokers and 82 who had quit smoking. This research was conducted in the Semarang City area, Central Java. This research was conducted in March-April 2024. The sample was selected using fixed disease sampling for active smoking participants and snowball sampling for participants who had quit smoking. The dependent variable is smoking cessation behavior. The independent variables are expectation of results, self-regulation, self-efficacy, and strengthening. Data collection was carried out using a questionnaire and the data was analyzed using a path analysis model. Results: Smoking cessation behavior increased with high self-efficacy (OR= 19.99; 95% CI= 7.46 to 53.62; p<0.001) and strong self-regulation (OR= 3.05; 95% CI= 1.51 to 6.13; p= 0.002). Self-efficacy increased with the expectation of positive results (OR= 8.64; 95% CI= 4.52 to 16.52; p<0.001) and strong self-regulation increases with strengthening (OR = 3.61; 95% CI= 1.99 to 6.53; p<0.001). Thus, social cognitive theory can be used to explain and predict smoking cessation behavior. Conclusion: Smoking cessation behavior increases with high self-efficacy, strong self-regulation, positive outcome expectations, and strengthening. Thus, social cognitive theory can be used to explain and predict smoking cessation behavior. Keywords: social cognitive theory, smoking cessation, early adulthood.